Bagaimana self-efficacy calon guru siswa dengan disabilitas di sekolah inklusi?: Studi di berbagai Perguruan Tinggi - Novembli, Meta Silfia; Azizah, Nur (Persona:Jurnal Psikologi Indonesia, 2020)
AbstractThe prospective teacher must have both academic and competency readiness. Besides, they must have self-efficacy on their own ability to later teach in schools, especially inclusive schools. However, until now research that discusses how Prospective teachers’ self-efficacy in teaching students with disabilities is still very limited and unclear. The purpose of this study is to reveal the self-efficacy profile of prospective teachers in teaching students with disabilities in inclusive schools as seen in three sub-constructs namely using inclusive instruction, collaboration, and managing behavior. The type of research is a survey. The population is the students of the Elementary School Teacher Education Study Program with a sample of 234 people. The data were collected using a scale of self-efficacy for prospective teachers with alpha coefficient 0,983. The data analyzed using descriptive statistics. In general, the self-efficacy of prospective teachers is in the moderate category. Based on the three sub-constructs of self-efficacy, prospective teachers in using inclusive instructional, collaboration, and managing behavior also are in a medium category. Implications may be reviewed further by the Ministry of Higher Education and University.Key Words: Prospective Teachers; Collaboration; Managing Behavior; Self-Efficacy; Using Inclusive InstructionAbstrakCalon guru harus mempunyai kesiapan baik akademik maupun kompetensi sebelum mengajar di sekolah. Selain itu, calon guru harus mempunyai self-efficacy atas kemampuannya sendiri untuk nantinya mengajar di sekolah terutama sekolah inklusi. Namun, hingga kini penelitian mengenai bagaimana self-efficacy calon guru untuk mengajar siswa dengan disabilitas masih sangat terbatas. Tujuan dari penelitian ini adalah menjelaskan gambaran self-efficacy calon guru untuk mengajar siswa dengan disabilitas di sekolah inklusi yang dilihat pada tiga sub konstruk yaitu using inclusive instructional, collaboration, dan managing behavior. Metode penelitian adalah survei dengan pendekatan kuantitatif. Populasi penelitian adalah mahasiswa Program Studi Pendidikan Guru Sekolah Dasar dengan partisipan sebanyak 234 orang. Pengumpulan data menggunakan skala self-efficacy calon guru dengan koefisien alpha 0,983. Analisis data menggunakan statistik deskriptif. Secara umum self-efficacy calon guru berada pada kategori sedang. Berdasarkan ketiga sub-konstruk self-efficacy calon guru yaitu dalam using inclusive instructional, collaboration, dan managing behavior juga memiliki kategori sedang. Implikasi dapat dikaji lebih lanjut oleh Kementerian Pendidikan Tinggi dan Universitas.Kata Kunci: Calon Guru; Kerja Sama; Manajemen Perilaku; Self-Efficacy; Pembelajaran Inklusif